2003
DOI: 10.1002/jccs.200300119
|View full text |Cite
|
Sign up to set email alerts
|

Vapor‐Phase Reaction of Citronellal over Mesoporous Molecular Sieves MCM‐41 and Zeolites

Abstract: The vapor-phase reaction of citronellal (CTN) at 220°C and atmospheric pressure has been studied using mesoporous molecular sieves and zeolites in a fixed-bed reactor. The primary products included isopulegol (IPG), menthone, and pulegol with subsequent reactions to form cyclic hydrocarbons. The CTN conversion and the product selectivity depend on the acidity and the textural property of catalysts. Lewis and/or Brönsted acid sites are essential for catalyzing this reaction. An increase of SiO2/Al2O3 mol ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The previous studies revealed that the catalytic results depend on several parameters such as acidity, pore size, and pore channel structure of catalysts. 2,3,[8][9][10]13,16,17,19,20 Stereoselectivity of ca. 60−80% to (−)-isopulegol was obtained, with the rest comprising racemates and byproducts, namely, of isopulegol dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies revealed that the catalytic results depend on several parameters such as acidity, pore size, and pore channel structure of catalysts. 2,3,[8][9][10]13,16,17,19,20 Stereoselectivity of ca. 60−80% to (−)-isopulegol was obtained, with the rest comprising racemates and byproducts, namely, of isopulegol dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Since M41S mesoporous molecular sieves were first reported by the Mobil group in 1992, 4,5 the synthesis, characterization and potential applications for adsorption, separation and catalysis of mesoporous materials have been widely investigated. 3 MCM-41 exhibits a highly ordered hexagonal array of one-dimensional mesopores, whose diameters can be varied from 15 to 100 Å with a narrow pore-size distribution through the adequate surfactant as the template and synthetic condition.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Figure 3 and According to an explanation in a previous work [28], p-mentha-3,8-diene may be a product of βcitronellal since the latter compound can be cyclized to result in isopulegol with byproducts including menthone, pulegol, and other cyclic hydrocarbons such as α-terpinene, p-mentha-3,8-diene and terpinolene.…”
Section: Gc-ms Analysis Of Tom Yum Soup and Compound Identificationmentioning
confidence: 75%